2009
DOI: 10.4103/0970-0358.59287
|View full text |Cite
|
Sign up to set email alerts
|

Treating transsexuals in India: History, prerequisites for surgery and legal issues

Abstract: Authors in their clinical practice came across transsexual patients, who were determined to get their gender affirmed by undergoing a change of sex. This motivated the authors to review the literature extensively regarding transsexualism and report their experience. Opinions were taken from legal luminaries practicing in related fields. They also took inputs from several patients who were at various stages of psychiatric analysis and hormone therapy and also those, who had completed their treatment procedures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, the question remains as to how far these most recent high standards of care for TS individuals can be interpreted and applied in culturally diverse countries with more traditional values. Indeed, in communities with more traditional values, the challenges faced by TS individuals differ from those faced by TS persons in urban western societies with a prescribed standard of care [12, 13]. In such societies, those who do not express their sexuality or gender in traditionally accepted ways may feel unwelcome [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the question remains as to how far these most recent high standards of care for TS individuals can be interpreted and applied in culturally diverse countries with more traditional values. Indeed, in communities with more traditional values, the challenges faced by TS individuals differ from those faced by TS persons in urban western societies with a prescribed standard of care [12, 13]. In such societies, those who do not express their sexuality or gender in traditionally accepted ways may feel unwelcome [14].…”
Section: Introductionmentioning
confidence: 99%
“…Meerwijk and Sevelius in their meta-analysis study published in 2017 revealed in the USA that 390/100,000 adults are estimated to be transgender. [ 6 ] No definite figures are available for India,[ 7 ] but transgender population is palpably on the rise.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] This may be related to the fact that their cultures do not view transsexualism as an expression of moral depravity but rather as an expression of the diverseness of nature, including human nature. It has been hypothesized that in cultures with a rigorous definition of manhood and womanhood, men who fail to fulfill the exigencies of manhood would resort to a transsexual state, but in the author's experience, this is not the case.…”
Section: Transsexualism/the Subjective Experiencementioning
confidence: 99%